Optimization of CuOx/Ga2O3 Heterojunction Diodes for High-Voltage Power Electronics - Xiaohui Wang; Mujun Li; Minghao He; Honghao Lu; Chun-Zhang Chen; Yang Jiang; Kangyao Wen; Fangzhou Du; Yi Zhang; Chenkai Deng; Zilong Xiong; Haozhe Yu; et al. (Nanomaterials)
This study optimizes the CuOx/Ga2O3 heterojunction diodes (HJDs) by tailoring the structural parameters of CuOx layers. The hole concentration in the sputtered CuOx was precisely controlled by adjusting the Ar/O2 gas ratio. Experimental investigations and TCAD simulations were employed to systematically evaluate the impact of the CuOx layer dimension and hole concentration on the electrical performance of HJDs. The results indicate that increasing the diameter dimension of the CuOx layer or tuning the hole concentration to optimal values significantly enhances the breakdown voltage (VB) of single-layer HJDs by mitigating the electric field crowing effects. Additionally, a double-layer CuOx structure (p+ CuOx/p− CuOx) was designed and optimized to achieve an ideal balance between the VB and specific on-resistance (Ron,sp). This double-layer HJD demonstrated a high VB of 2780 V and a low Ron,sp of 6.46 mΩ·cm2, further yielding a power figure of merit of 1.2 GW/cm2. These findings present a promising strategy for advancing the performance of Ga2O3 devices in power electronics applications.